2016
DOI: 10.12659/msm.899950
|View full text |Cite
|
Sign up to set email alerts
|

Thioridazine Sensitizes Esophageal Carcinoma Cell Lines to Radiotherapy-Induced Apoptosis In Vitro and In Vivo

Abstract: BackgroundRadiotherapy is one of the primary treatments for esophageal squamous cell carcinoma (ESCC). Identification of novel radio-sensitizing agents will improve the therapeutic outcome of radiotherapy. This study aimed to determine the radio-sensitizing effect of the antipsychotic agent thioridazine in ESCC and explored the underlying mechanisms.Material/MethodsECA-109 and TE-1 ESCC cells were treated with thioridazine and radiotherapy alone and in combination. Cell survival was measured by MTT assay. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Consistently, the expression of several YAP-target genes (e.g., CTGF, Zeb1, Twist1) that drive EMT and invasiveness of these cells was suppressed in the NEK1-KO clones [24], and there was no apparent compensation from other NEKs, which are not reported to act on YAP [103]. We have also tested by qRT-PCR the expression of several of these genes in LNCaP and C2 cells treated with BIC+J54, but in that case, the main effect was a dramatic 70-fold increase in BAX [49], confirming an effect previously reported in response to PTHs treatment of cancer cells [104]. This suggests that any residual YAP switches to the YAP/P73 transcriptional complex that implements the apoptotic program in response to DNA damage [105].…”
Section: Tlk1 In Pca Progressionsupporting
confidence: 85%
“…Consistently, the expression of several YAP-target genes (e.g., CTGF, Zeb1, Twist1) that drive EMT and invasiveness of these cells was suppressed in the NEK1-KO clones [24], and there was no apparent compensation from other NEKs, which are not reported to act on YAP [103]. We have also tested by qRT-PCR the expression of several of these genes in LNCaP and C2 cells treated with BIC+J54, but in that case, the main effect was a dramatic 70-fold increase in BAX [49], confirming an effect previously reported in response to PTHs treatment of cancer cells [104]. This suggests that any residual YAP switches to the YAP/P73 transcriptional complex that implements the apoptotic program in response to DNA damage [105].…”
Section: Tlk1 In Pca Progressionsupporting
confidence: 85%
“…Consistently, the expression of several YAP-target genes (e.g., CTGF, Zeb1, Twist1) that drive EMT and invasiveness of these cells was suppressed in the NEK1-KO clones [103], and there was no apparent compensation from other NEKs, which are not reported to act on YAP [105]. We have also tested by qRT-PCR the expression of several of these genes in LNCaP and C2 cells treated with BIC+J54, but in that case, the main effect was a dramatic 70-fold increase in BAX [100], confirming an effect previously reported in response to PTHs treatment of cancer cells [106]. This suggests that any residual YAP switches to the YAP/P73 transcriptional complex that implements the apoptotic program in response to DNA damage [107].…”
Section: Tlk1 In Pca Progressionsupporting
confidence: 85%
“…Firstly, we selected two ESCC cell lines, KYSE-30 and TE-1, which expressed the vascular endothelial growth factor receptor, VEGFR-2. 20,21 As shown in Figure 1A, Western blot result indicated that VEGFR-2 was detected in both KYSE-30 and TE-1 cells, with the HUVEC cell line used as the positive control for VEGFR-2 expression. Next, we examined how apatinib and raltitrexed treatments change the proliferation capacity of KYSE-30 and TE-1 cells.…”
Section: Raltitrexed Enhances the Inhibitory Effects Of Apatinib On Cmentioning
confidence: 98%